2018
DOI: 10.1016/j.cogdev.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Episodic memory in middle childhood: Age, brain electrical activity, and self-reported attention

Abstract: Middle childhood is a transitional period for episodic memory (EM) performance, as a result of improvements in strategies that are used to encode and retrieve memories. EM is also a skill continually assessed for testing in the school setting. The purpose of this study was to examine EM performance during middle childhood and its relation to individual differences in attentional abilities and in neurophysiological functioning. We examined self-reports of attention at 6, 7 and 8-years of age as well as parietal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…While we did not have specific hypotheses about laterality effects, we found that only left parietal theta activation during retrieval predicted memory binding performance. In a study examining EEG correlates of item recognition memory in middle childhood, Diaz et al (2018) report similar findings; only posterior parietal EEG in the left hemisphere was associated with individual differences in performance. The question of laterality effects needs to be further explored.…”
Section: Theta Eeg and Memory Processesmentioning
confidence: 63%
See 1 more Smart Citation
“…While we did not have specific hypotheses about laterality effects, we found that only left parietal theta activation during retrieval predicted memory binding performance. In a study examining EEG correlates of item recognition memory in middle childhood, Diaz et al (2018) report similar findings; only posterior parietal EEG in the left hemisphere was associated with individual differences in performance. The question of laterality effects needs to be further explored.…”
Section: Theta Eeg and Memory Processesmentioning
confidence: 63%
“…In a study examining EEG correlates of item recognition memory in middle childhood, Diaz et al. (2018) report similar findings; only posterior parietal EEG in the left hemisphere was associated with individual differences in performance. The question of laterality effects needs to be further explored.…”
Section: Discussionmentioning
confidence: 78%
“…The works devoted to the study of memory and attention turned out to be quite numerous. There are no found correlation between age and attention levels in children of 6-8 ages by A. Diaz et al [6], but the memorization and retrieval skills of older children were higher. The difference in skills of active controlled retrieval between children and adults was noted by F. Simard and G. Cadoret [7]: in the process of solving the active controlled retrieval task, a lower level of memorization and retrieval skills was revealed in children compared to adults.…”
Section: Review Of Research Papersmentioning
confidence: 85%
“…), while implicit retrieval also involves the motor system regions. The early development of memory is mainly related to the development of the medial temporal lobe in early-life, while the late development of memory is related to the development of the frontoparietal control network in adolescence 的激活程度和情景记忆表现呈正相关 [47] . 一项ERP (event-related potential)研究发现, 不同于成年人群体 中新旧效应主要包括早期的前额中区成分和晚期的顶 区成分 [78] , 儿童群体只有顶区的新旧效应, 且儿童比 成年人有更长的潜伏期 [79] .…”
Section: 从儿童到成年 工作记忆能力逐渐提高 如有研究 显示 18~38岁的成年人群体比6~13岁的儿童群体有mentioning
confidence: 99%